Sutureless Intrascleral Haptic-Hook Lens Implantation Using 25-Gauge Trocars - Zhi-Xiang Hu; HaiShuang Lin; Lingying Ye; Zhong Lin; Tianyu Chen; Ke Lin; Rong-Han Wu (Journal of Ophthalmology)
Purpose. To report a new technique for sutureless intrascleral fixation of three-piece foldable intraocular lenses (IOLs) using 25-gauge trocars. Methods. We performed this technique on patients with insufficient posterior capsule support. Seventeen eyes from 15 patients with aphakia, dislocated IOL, or subluxated crystalline lens undergoing posterior chamber sutureless implantation of an IOL were studied. The haptics of the IOL were externalized using two 25-gauge forceps. The haptics were bended back (hook-like) into the vitreous cavity through a scleral incision made by using a 25-gauge trocar. And, IOL tilt was determined by using a slit lamp and UBM, and complications were recorded. Results. The IOLs were fixed with exact centration and axial stability. No wound leakage was reported even without the use of sutures. The mean best-corrected visual acuity (BCVA) was 0.82 logarithm of the minimum angle of resolution (logMAR) units preoperatively, and the mean BCVA was 0.44 logMAR units at the 6-month follow-up visit. No postoperative retinal detachment, endophthalmitis, IOL tilt or dislocation, or vitreous hemorrhage was noted. Conclusion. Sutureless intrascleral haptic-hook posterior chamber IOL implantation using 25-gauge trocars provides good IOL fixation with reliable wound closure without the use of sutures. This trial is registered with ChiCTR1800017436.